Pengaruh Motivasi Terhadap Semangat Kerja Pegawai Honorer Pada Dinas Pendidikan Kabupaten Pelalawan - Sudarmin Manik; Nova Syafrina; Abasri Abasri (Universitas Negeri Padang, 2019)
This research was conducted at Pelalawan District Education Office. With the aim of research to find out. In the field of education and education. The population in this study were all civil servants at the district level, while the sample in this study amounted to 95 honorary employees. Data analysis used is validity test, reliability test, normality test, simple linear regression test and determination coefficient test. While hypothesis testing uses t test. The result of the research is that these variables give very positive and significant results to tcount values of 10,340> t table 1,985 with a significance level of 0,000 smaller than 0.05. In simple linear regression, the equation Y = 15,223 + 0,843X is obtained. Whereas in the test the determination coefficient of R square value is 0.535, this means that the variable work motivation (X) contributes to the working spirit of the employees of the Education Office of Pelalawan Regency by 53.50%